Nanomaterials targeting macrophages in sepsis: A promising approach for sepsis management - Song, Chaoying; Xu, Jiqian; Gao, Chenggang; Zhang, Wanying; Fang, Xiangzhi; Shang, You (Frontiers in Immunology, 2022)
Sepsis is a life-threatening organ dysfunction resulting from dysregulated host responses to infection. Macrophages play significant roles in host against pathogens and the immunopathogenesis of sepsis, such as phagocytosis of pathogens, secretion of cytokines, and phenotype reprogramming. However, the rapid progression of sepsis impairs macrophage function, and conventional antimicrobial and supportive treatment are not sufficient to restore dysregulated macrophages roles. Nanoparticles own unique physicochemical properties, surface functions, localized surface plasmon resonance phenomenon, passive targeting in vivo, good biocompatibility and biodegradability, are accessible for biomedical applications. Once into the body, NPs are recognized by host immune system. Macrophages are phagocytes in innate immunity dedicated to the recognition of foreign substances, including nanoparticles, with which an immune response subsequently occurs. Various design strategies, such as surface functionalization, have been implemented to manipulate the recognition of nanoparticles by monocytes/macrophages, and engulfed by them to regulate their function in sepsis, compensating for the shortcomings of sepsis traditional methods. The review summarizes the mechanism of nanomaterials targeting macrophages and recent advances in nanomedicine targeting macrophages in sepsis, which provides good insight for exploring macrophage-based nano-management in sepsis.